INTERPRETACJA W PRAWIE I W SZTUCE JAKO PRZEJAW OGÓLNEJ INTERPRETACJI HUMANISTYCZNEJ - Żurawik, Artur (Wydział Prawa i Administracji UAM, 2001)
The article embraces two strictly interconnected problems: the problem of interpretative openness and closedness as well as the issue of interpretative determinants. This issue is preceded by introductory and systematising remarks, specifically concerning the way of understanding law and art, defining legal text and image, as well as the linguistic aspect of both of these transmission forms. The presented description of interpretation appears to bear out the statement that interpretation in law and art, despite the doubtless distance between the two areas, is based upon similar principles and they both are therefore a peculiar form of generally humanistic interpretation. The hermeneutical method is applicable in interpreting such various phenomena, and maybe only interpretation of legal text is more strict, which is a result o f the interpretative closedness postulate. In both cases all the main principles of the hermeneutical method are realised: 1) the linguistic dimension of understanding, 2) its historicity, 3) the principle o f the hermeneutical circle expressed in the division of determinants into inherent and contextual, 4) preliminary understanding of the interpreter, 5) application (dynamic view of interpretation allowing for changes of reality context).
INTERPRETATION IN LAW AND ART AS A MANIFESTATION OF GENERAL HUMANISTIC INTERPRETATION